STUDY OF THE DEPENDENCE OF GAMMA-ABSORPTIONCOEFFICIENT ON THE ORDER OF THE DOUBLE LAYER SHIELD - Al-Bayati, Abdul-Hussein (Iraqi Journal of Science, 2024)
Gamma absorption coefficient dependence on the order of the shieldingmaterial is measured using a proper electronic system and Cs-137 source. Themeasurements were carried out for iron, steel, copper, brass, lead and concrete asshielding materials.The dependence of gamma absorption coefficient on the atomic number and densityof the absorber material is taken into account. The experimental and theoreticalcalculations are in a good agreement.It is found that the absorption coefficient value increases with increasing theabsorber thickness of high atomic number (or density) and decreases with increasingthe absorber thickness of low atomic number (or density), and slightly changes withincreasing the thickness of any absorber when the difference between their atomicnumber (or density) is small, whereas it is affected by the order of the two-layerabsorber if the difference between their atomic number is high.